2014
DOI: 10.1016/j.numecd.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of peripheral arterial disease in diabetes: A consensus of the Italian Societies of Diabetes (SID, AMD), Radiology (SIRM) and Vascular Endovascular Surgery (SICVE)

Abstract: Diabetic foot (DF) is a chronic and highly disabling complication of diabetes. The prevalence of peripheral arterial disease (PAD) is high in diabetic patients and, associated or not with peripheral neuropathy (PN), can be found in 50% of cases of DF. It is worth pointing out that the number of major amputations in diabetic patients is still very high. Many PAD diabetic patients are not revascularised due to lack of technical expertise or, even worse, negative beliefs because of poor experience. This despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 132 publications
0
61
0
7
Order By: Relevance
“…In diabetic subjects, peripheral arterial disease more frequently affects below-the-knee vessels such as the tibial and peroneal arteries and is symmetric, multi-segmental while the collateral vessels can also be affected by stenosis. 14 Our study has shown that all patients presented with peripheral arterial disease, i.e. underlying tibioperoneal disease (77%).…”
Section: Discussionmentioning
confidence: 70%
“…In diabetic subjects, peripheral arterial disease more frequently affects below-the-knee vessels such as the tibial and peroneal arteries and is symmetric, multi-segmental while the collateral vessels can also be affected by stenosis. 14 Our study has shown that all patients presented with peripheral arterial disease, i.e. underlying tibioperoneal disease (77%).…”
Section: Discussionmentioning
confidence: 70%
“…In diabetic pts, PAD is usually symmetrical and multi-segmental and involves arteries below the knee [20]. Moreover, the arterial walls are often calcified and occlusions are more frequent than stenosis [21]. PAD progression, defined as ABI decline >0.15 is significantly associated with both all-cause and CV mortality [22].…”
Section: Epidemiology and Clinical Characteristics Of Padmentioning
confidence: 99%
“…In case of significant stenosis or ulcerated plaque, MRI or TC could be help clinician to better define arterial disease and the need of treatment. In fact, carotid stenosis > 70% or ulcerated plaque should be treated before treating limb ischemia [68].…”
Section: Assessment Therapy In Case Of Revascularizationmentioning
confidence: 99%